Intermediate cities: a Mexico-China comparison (2020)
Since their economic reforms, Mexico and China have registered a rapid urban expansion that modified the distribution of the urban system leading to a higher relative weight of the intermediate cities. This paper aims to examine the cities’ size dispersion for both economies in 2005 and 2010, respectively. The original and adjusted range-size equation is used in addition to an econometric methodology of Ordinary Least Squares of mobile ranges to estimate the Pareto coefficient. The size is defined according to each city’s GDP of at least 15, 000 inhabitants, instead of using the population as a measure of size, representing an original aspect of the paper. The hypothesis is a Pareto exponent lower than the unit. Estimates by subsamples suggest the existence of relatively equal size distribution of cities in both nations. As the main intermediate cities are grouped into comparatively equitable urban systems, it is accepted that the higher relative economic weight of intermediate cities explains the deviation of the exponent. The main limitation is the availability of data which means a disparity of years between economies.